TapOnce: a novel authentication method on smartphones. Issue 1 (3rd April 2018) - Inoue, Minori; Ogawa, Takefumi
Abstract : Purpose: Security technology on mobile devices is increasingly more important as smartphones are becoming more versatile and, thus, store more sensitive information. Among the three indispensable factors of owner authentication technologies on mobile devices, security, usability and system efficiency, usability is considered the key factor. This paper aims to challenge the limits of usability on mobile device authentication technology with respect to input size. Design/methodology/approach: This paper introduces one tap authentication as a novel authentication method on mobile devices. A user just has to tap the screen of a smartphone once, and he or she will be authenticated. Findings: One tap authentication is proven possible in this paper. The average equal error rate among 10 owners against 25 unauthorized users is as low as 3.8. Research limitations/implications: This paper focuses on verifying the possibility on one tap authentication. However, the application to various environments, such as when standing or walking or on a train, is not explored. Originality/value: This research explores tap authentication with a single tap for the first time in the field. To the best of the authors' knowledge, the minimum number of taps required in tap authentication has been 4.